A Check List of Ethnomedicinal Plants Used by Ethnic Communities of Jorhat District of Assam, India - Dutta, Ankur Jyoti; Sinha, Darshita; Konwar, Surajeet (Asian Journal of Biological and Life Sciences)
This study aims to document the ethnomedicinal plants used by ethnic communities in the Jorhat district of Assam, India. Indigenous knowledge about medicinal plants is a crucial part of traditional healthcare practices, yet much of this knowledge remains undocumented. The objective is to create a checklist of plants, detailing their local uses, to provide a resource for future phytochemical studies and promote the conservation of both the plants and the cultural knowledge associated with them. Field surveys were conducted in various regions of Jorhat from 2022 to 2023, focusing on areas populated by ethnic groups. Information on medicinal plants was collected through interviews with knowledgeable community members, such as elders and herbal practitioners. Plant specimens were identified with the help of local floras and the information was cross-verified across multiple informants and existing literature. A total of 125 plant species with 60 genera were documented, each classified by family, local name, plant part used and traditional medicinal application. The plants are employed to treat various ailments ranging from digestive issues and respiratory diseases to skin disorders and infections. The ethnomedicinal knowledge of Jorhat’s ethnic communities holds great potential for contributing to modern healthcare, particularly in drug discovery. The catalogued plant species could serve as a valuable resource for researchers seeking bioactive compounds, while the study underscores the need for conservation efforts to protect both biodiversity and indigenous knowledge.
Keywords: Ethnomedicine; Traditional Knowledge; Tribe; Treatments